Novel lithium metal battery ether electrolyte and preparation method thereof
By using a specific combination of non-aqueous organic solvents and additives in lithium metal batteries, a stable SEI film is formed, solving the problems of dendrite growth and interface stability, and achieving battery performance with high energy density and long cycle life.
Patent Information
- Application Number
- CN202511201896.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-26
- Publication Date
- 2025-12-12
Smart Images

Figure CN121123394A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of electrochemical energy storage, in particular to a novel ether-based electrolyte for lithium metal batteries and a preparation method thereof. BACKGROUND
[0002] Commercial lithium-ion batteries use graphite as the anode material, with a theoretical specific capacity of only 372 mAh g -1 , which has been difficult to meet the demand for higher energy density. In contrast, metal lithium has a theoretical specific capacity of up to 3890 mAh g -1 and a minimum reduction potential of -3.04 V (vs. SHE), which is generally considered by the industry as an ideal anode material for the next generation of high specific capacity batteries. However, during charging and discharging, metal lithium is prone to dendrite growth, uneven growth and the formation of "dead lithium", and also continuously reacts with the electrolyte, resulting in low coulombic efficiency, limited cycle life, and even safety hazards.
[0003] To inhibit lithium dendrites and improve interface stability, researchers have widely tried to introduce ether solvents with low viscosity and low solvation energy, or to increase the concentration of lithium salt to form high-concentration / local high-concentration electrolyte, in addition to the traditional carbonate system. The above strategies can promote uniform deposition and generate a solid-state electrolyte interface (SEI) rich in inorganic salt components to some extent, but still face problems such as increased viscosity, limited low-temperature kinetics, higher flammability, and insufficient oxidation stability at high voltage.
[0004] On the other hand, the addition of functional lithium salts or trace additives in ether-based systems has been shown to further strengthen the composition and structure of the SEI. However, multi-component formulations often lead to increased costs and process complexity; some chlorine- and sulfur-containing components may also introduce corrosive and environmental adaptability risks.
[0005] In summary, existing electrolytes still have obvious deficiencies when considering performance indicators such as high ionic conductivity, low viscosity, wide electrochemical window, and stable SEI generation. Developing an ether-based electrolyte formulation with high conductivity, low viscosity, and excellent interface stability to achieve long cycle life and high safety of metal lithium batteries under high current density and high surface capacity conditions is still a key technical problem that needs to be solved by those skilled in the art. SUMMARY
[0006] The present application provides a novel ether-based electrolyte for lithium metal batteries and a preparation method thereof, aiming to solve the technical problems of easy growth of lithium dendrites, poor interface stability, excessive viscosity, and insufficient cycle safety in the prior art.
[0007] To achieve the above-mentioned purposes, the technical solutions of the present application are as follows:
[0008] In a first aspect, the present application provides a novel ether-based electrolyte for lithium metal batteries, the components of the electrolyte including a non-aqueous organic solvent system, a lithium salt, and an additive.
[0009] The non-aqueous organic solvent system includes at least one of ethylene glycol dimethyl ether, 1,3-dioxolane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethyl ether, propyl ether, butyl ether, tetrahydrofuran, tetrahydropyran, vinyl carbonate, fluorinated vinyl carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.
[0010] The lithium salt includes at least one of lithium bisfluorosulfonylimide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluoro(oxalato)borate, lithium hexafluorophosphate, lithium tetrafluoroborate.
[0011] The additive includes at least one of vinylene carbonate, fluorinated vinyl carbonate, propane sultone, lithium nitrate, lithium difluoro(oxalato)borate, tris(pentafluorophenyl)borane, tris(pentafluorophenyl)phosphane, pentafluorophenoxy cyclotriphosphazene.
[0012] Further, the non-aqueous organic solvent system includes ethylene glycol dimethyl ether and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and the volume ratio of ethylene glycol dimethyl ether to 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether ranges from 1-3:1.
[0013] Further, the concentration of the lithium salt in the electrolyte ranges from 0.1-5 mol / L.
[0014] Further, the additive includes lithium nitrate, lithium difluoro(oxalato)borate, tris(pentafluorophenyl)borane, and pentafluorophenoxy cyclotriphosphazene, and the content of lithium nitrate, lithium difluoro(oxalato)borate, and tris(pentafluorophenyl)borane each accounts for 2wt% of the total mass of the electrolyte, and the content of pentafluorophenoxy cyclotriphosphazene accounts for 2-6wt% of the total mass of the electrolyte.
[0015] In a second aspect, the present application provides a preparation method of the novel ether-based electrolyte for lithium metal batteries, including:
[0016] Under an inert atmosphere, the solvents in the non-aqueous organic solvent system are mixed in a predetermined volume ratio, and are subjected to magnetic stirring at 20-35℃ for 10-30 min to obtain a uniform solvent matrix;
[0017] The lithium salt is added to the solvent matrix in batches while continuously stirring, the solution temperature is controlled to be ≤40℃, and the solution is stirred for 0.5-2h until the lithium salt is completely dissolved;
[0018] The additives are added in sequence, and stirring is continued for 12-48 h to make them fully dissolved and dispersed, to obtain the ether electrolyte.
[0019] Further, the inert atmosphere is argon, nitrogen or helium.
[0020] Further, the ether electrolyte is filtered through a polytetrafluoroethylene microporous membrane with a pore size of 0.20-0.45 μm under an inert atmosphere.
[0021] In a third aspect, the application provides a use of the novel ether electrolyte for lithium metal batteries in a lithium symmetric battery,
[0022] The negative electrode and the positive electrode of the battery are both lithium metal sheets or lithium alloy sheets.
[0023] The battery separator of the battery is polyethylene or polypropylene.
[0024] The electrolyte of the battery is the novel ether electrolyte for lithium metal batteries described above.
[0025] In a fourth aspect, the application provides a use of the novel ether electrolyte for lithium metal batteries in a lithium asymmetric battery,
[0026] The negative electrode of the battery is a lithium metal sheet or a lithium alloy sheet.
[0027] The positive electrode of the battery is a copper foil.
[0028] The battery separator of the battery is polyethylene or polypropylene.
[0029] The electrolyte of the battery is the novel ether electrolyte for lithium metal batteries described above.
[0030] In a fifth aspect, the application provides a use of the novel ether electrolyte for lithium metal batteries in a lithium full battery,
[0031] The negative electrode of the battery is a lithium metal sheet or a lithium alloy sheet.
[0032] The positive electrode of the battery is lithium iron phosphate.
[0033] The battery separator of the battery is polyethylene or polypropylene.
[0034] The electrolyte of the battery is the novel ether electrolyte for lithium metal batteries described above.
[0035] Compared with the prior art, the application has the following beneficial effects:
[0036] The application significantly improves the stability of the lithium metal negative electrode interface in a high-concentration LiFSI ether system by precisely regulating the solvent ratio and introducing multifunctional additives containing fluorine and nitrate, etc. The experimental results show that, under the same salt concentration, the cycle life of lithium symmetric and asymmetric batteries is multiplied after changing the single DME solvent to a DME / DOL or DME / TTE binary system; further combined with LiNO3, LiDFOB, TPFPP, TPFPB and PFPN additives, the Li||Li battery can be stably operated for more than 1,000 hours under the condition of 1mAcm -2 , and still maintains the deposition-stripping stability for several hundred hours under the high current density of 5-10mAcm -2 . Compared with the control group without additives, the above-mentioned optimized system slightly increases the interface impedance, but the use of perfluoro diluent TTE can effectively reduce the impedance and maintain high ionic conductivity, showing excellent large-current adaptation ability.
[0037] Raman spectrum analysis shows that the functional additives induce the formation of a composite SEI rich in fluorine and inorganic components on the lithium surface, and the solvation structure is transformed from solvent-separated ion pairs to contact ion pairs and aggregates, which helps to inhibit dendrite growth and reduce side reactions. Full-cell tests further prove that the electrolyte is well matched with the LFP positive electrode system, and can balance high coulombic efficiency and excellent capacity retention rate at 0.1C and 1C rates. In summary, the electrolyte of the application maintains high energy density while realizing low impedance, high conductivity and long cycle life, providing an effective solution for the safe and reliable operation of metal lithium batteries under harsh working conditions such as high surface capacity and high current density.
[0038] Of course, implementing each technical solution of the application does not necessarily need to achieve all the advantages described above. BRIEF DESCRIPTION OF DRAWINGS
[0039] In order to more clearly illustrate the technical solutions in the embodiments of the application or the prior art, the following will briefly introduce the drawings needed to be used in the embodiments or prior art description. Obviously, the drawings in the following description only constitute some embodiments of the application, and for those skilled in the art, other drawings can also be obtained from these drawings without creative labor.
[0040] Figure 1 is the performance of symmetric battery under different current densities of 2M LiFSI-DME of the application embodiment 2M LiFSI-DME;
[0041] Figure 2 is the performance of asymmetric battery under different current densities of 2M LiFSI-DME of the application embodiment 2M LiFSI-DME;
[0042] Figure 3This describes the performance of the asymmetric battery 2M LiFSI-DME:DOL-2:1 under different current densities in Embodiment 2 of the present invention.
[0043] Figure 4 This describes the performance of the asymmetric battery 2M LiFSI-DME:DOL-2:1 under different current densities in Embodiment 2 of the present invention.
[0044] Figure 5 This describes the performance of a symmetrical battery under different current densities in Example 2 of the present invention, namely, LiFSI-DME:DOL-2:1+2%LiNO3+2%LiDFOB+2%TPFPP+2%TPFPB.
[0045] Figure 6 This describes the performance of an asymmetric battery under different current densities in Example 2MLiFSI-DME:DOL-2:1+2%LiNO3+2%LiDFOB+2%TPFPP+2%TPFPB of the present invention.
[0046] Figure 7 This invention relates to the full cell performance of 2M LiFSI-DME:DOL-2:1+2%LiNO3+2%LiDFOB+2%TPFPP+2%TPFPB under different current densities in Example 2 of the present invention.
[0047] Figure 8 This describes the symmetrical battery performance of 2M LiFSI-DME:TTE-2:1+2%LiNO3+2%LiDFOB+2%TP FPP+2%TPFPB under different current densities in this invention.
[0048] Figure 9 This describes the performance of an asymmetric battery under different current densities in Example 2M of the present invention, LiFSI-DME:TTE-2:1+2%LiNO3+2%LiDFOB+2%TP FPP+2%TPFPB.
[0049] Figure 10 This describes the full cell performance of the 2M LiFSI-DME:TTE-2:1+2%LiNO3+2%LiDFOB+2%TPFPP+2%TPFPB under different current densities in Example 2 of the present invention.
[0050] Figure 11 This describes the performance of a symmetrical battery under different current densities in Example 2M of the present invention, LiFSI-DME:TTE-2:1+2%LiNO3+2%LiDFOB+6%PFPN+2%TPFPB.
[0051] Figure 12This describes the performance of an asymmetric battery under different current densities in Example 2M of the present invention, LiFSI-DME:TTE-2:1+2%LiNO3+2%LiDFOB+6%PFPN+2%TPFPB.
[0052] Figure 13 This describes the full cell performance of the 2M LiFSI-DME:TTE-2:1+2%LiNO3+2%LiDFOB+6%PFPN+2%TPFPB under different current densities in Example 2 of the present invention.
[0053] Figure 14 This is an impedance comparison diagram of five electrolytes in embodiments of the present invention;
[0054] Figure 15 These are the Raman spectra of the five electrolytes in the embodiments of the present invention. Detailed Implementation
[0055] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments. Similar elements in different embodiments are referred to by associated similar element reference numerals. In the following embodiments, many details are described to facilitate a better understanding of the present application. However, those skilled in the art will readily recognize that some features may be omitted in different situations, or may be replaced by other elements, materials, or methods. In some cases, certain operations related to the present application are not shown or described in the specification. This is to avoid obscuring the core parts of the present application with excessive description. For those skilled in the art, detailed description of these related operations is not necessary; they can fully understand the related operations based on the description in the specification and general technical knowledge in the art.
[0056] Furthermore, the features, operations, or characteristics described in the specification can be combined in any suitable manner to form various embodiments. At the same time, the steps or actions in the method description can be rearranged or adjusted in a manner obvious to those skilled in the art. Therefore, the various orders in the specification and drawings are only for the clear description of a particular embodiment and do not imply a necessary order, unless otherwise stated that a particular order must be followed.
[0057] For ease of discussion, the abbreviations of some of the raw materials involved in this invention are summarized below:
[0058] I. Non-aqueous organic solvent systems:
[0059] Ethylene glycol dimethyl ether (DME), 1,3-dioxolane (DOL), diethylene glycol dimethyl ether (Di-glyme), triethylene glycol dimethyl ether (Tri-glyme), tetraethylene glycol dimethyl ether (Tetra-glyme), diethylene glycol dimethyl ether (DGME), triethylene glycol dimethyl ether (TGME), tetraethylene glycol dimethyl ether (TeGME), tetrahydrofuran (THF), tetrahydropyran (THP), ethylene carbonate (EC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE).
[0060] II. Lithium Salts:
[0061] Lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorooxalateborate (LiDFOB), lithium hexafluorophosphate (LiPF6), and lithium tetrafluoroborate (LiBF4).
[0062] III. Functional Additives:
[0063] Vinylene carbonate (VC), fluoroethylene carbonate (FEC), propane sulfonate lactone (PS), lithium nitrate (LiNO3), lithium difluorooxalate borate (LiDFOB), tris(pentafluorophenyl)borane (TPFPB), tris(pentafluorophenyl)phosphine (TPFPP), and pentafluorophenoxycyclotriphosphazene (PFPN).
[0064] This invention provides a novel method for preparing an ether-based electrolyte for lithium metal batteries, comprising:
[0065] Step S1: The solvents in the non-aqueous organic solvent system are subjected to... Molecular sieve drying for ≥24h, water content ≤20ppm; under an inert atmosphere, the inert atmosphere is argon, nitrogen or helium; the solvents in the non-aqueous organic solvent system are mixed according to a predetermined volume ratio, and magnetically stirred at 20-35℃ for 10-30min to obtain a uniform solvent matrix;
[0066] Step S2: Add lithium salt in batches while continuously stirring the solvent matrix, control the solution temperature to ≤40℃ and stir for 0.5-2h until the lithium salt is completely dissolved;
[0067] Step S3: Add the additives sequentially and stir continuously for 12-48 hours to fully dissolve and disperse them, thus obtaining the ether electrolyte.
[0068] To further remove trace suspended matter, the ether electrolyte from step S3 was filtered through a 0.20-0.45 μm polytetrafluoroethylene microporous membrane under an inert atmosphere. Finally, the filtered electrolyte was transferred to a pre-dried and argon-filled aluminum-plastic composite bottle or polymer bottle, argon-filled and sealed, and stored in a cool, dark place.
[0069] The following examples further illustrate several different types of ether electrolytes of the present invention and the batteries thereof.
[0070] Example 1:
[0071] In this embodiment, a “2MLiFSI-DME” electrolyte was prepared in an inert argon glove box using dimethoxyethane (DME) as the single solvent and lithium bisfluorosulfonylimide (LiFSI) as the single lithium salt at a concentration of 2 mol·L⁻¹, without the addition of any functional additives. Subsequently, lithium symmetric batteries (Li||Li) and lithium asymmetric batteries (Li||Cu) were assembled sequentially, and their cycle stability was investigated.
[0072] The following detailed steps illustrate the preparation and testing process of this embodiment to verify the technical effect of the electrolyte in suppressing lithium dendrite growth and improving coulombic efficiency under high current density conditions.
[0073] Assembling a button-type lithium-ion symmetric battery: A battery casing of model 2025 and a polyethylene separator were selected. Both the negative and positive electrodes used lithium sheets with a thickness of 150-300 μm. The polyethylene separator was placed between the positive and negative electrodes, and 50 μL of the prepared electrolyte was dropped onto each side. Finally, the battery was encapsulated to obtain a button-type lithium-ion battery. The assembled battery was subjected to Li||Li symmetric battery cycle performance testing on a Newway testing instrument under the test conditions of 1 mA / 1 mAh. Results regarding 2M LiFSI-DME are as follows... Figure 1 As shown, it can be stably cycled for 650 hours at 1mA / 1mAh.
[0074] Assembling a button-type lithium asymmetric battery: A battery casing of model 2025 and a polyethylene separator were selected. The negative electrode used a lithium sheet with a thickness of 150-300μm, and the positive electrode was copper foil. The polyethylene separator was placed between the positive and negative electrodes, and 50μL of the prepared electrolyte was dropped onto each side. Finally, the battery was encapsulated to obtain a button-type lithium battery. The assembled battery was subjected to Li||Cu asymmetric battery cycle performance tests on a Newway testing instrument under the following conditions: 1mA / 1mAh, 2mA / 2mAh, 5mA / 5mAh, and 10mA / 10mAh. Results for 2M LiFSI-DM E are as follows... Figure 2 As shown, it can be stably cycled for 300h and 150h at 1mA / 1mAh and 2mA / 2mAh, respectively, but only for 110h and 60h at 5mA / 5mAh and 10mA / 10mAh, respectively.
[0075] Example 2:
[0076] In this embodiment, the single solvent system of Example 1 was replaced with a binary ether system composed of dimethoxyethane (DME) and 1,3-dioxolane (DOL) in a volume ratio of 2:1. LiFSI was still used as the lithium salt, with a concentration of 2 mol L⁻¹, and no functional additives were added. Thus, a “2M LiFSI-DME / DOL (2:1)” electrolyte was prepared. Subsequently, lithium symmetric batteries (Li||Li) and lithium asymmetric batteries (Li||Cu) were assembled in the same way to evaluate the effect of the binary ether system on improving cycle stability.
[0077] Assembling a button-type lithium symmetric battery: A battery casing of model 2025 and a polyethylene separator were selected. Both the negative and positive electrodes used lithium sheets with a thickness of 150-300μm. The polyethylene separator was placed between the positive and negative electrodes, and 50μL of the prepared electrolyte was dropped onto each side. Finally, the battery was encapsulated to obtain a button-type lithium battery. The assembled battery was subjected to Li||Li symmetric battery cycle performance testing on a Newway testing instrument under the test conditions of 1mA / 1mAh. Results regarding 2M LiFSI-DME:DOL-2:1 are as follows... Figure 3 As shown, it can be stably cycled for 1400 hours at 1mA / 1mA. This is an improvement over Example 1.
[0078] Assembling a button-type lithium asymmetric battery: A battery casing of model 2025 and a polyethylene separator were selected. The negative electrode used a lithium sheet with a thickness of 150-300μm, and the positive electrode was copper foil. The polyethylene separator was placed between the positive and negative electrodes, and 50μL of the prepared electrolyte was dropped onto each side. Finally, the battery was encapsulated to obtain a button-type lithium battery. The assembled battery was subjected to Li||Cu asymmetric battery cycle performance tests on a Newway testing instrument. The test conditions were 1mA / 1mAh, 2mA / 2mAh, 5mA / 5mAh, and 10mA / 10mAh. The results for 2MLiFSI-DM E are as follows... Figure 4 As shown, it can cycle stably for 400 hours at 1 mA / 1 mAh and is still cycling, and it cycles for 250 hours at 2 mA / 2 mAh, but only for 150 hours and 45 hours at 5 mA / 5 mAh and 10 mA / 10 mAh, respectively.
[0079] Example 3:
[0080] Under the conditions of the binary ether system in Example 2, this example further incorporates 2 mol L- 1Lithium nitrate (LiNO3), lithium difluorooxalate borate (LiDFOB), tris(pentafluorophenyl)phosphine (TPFPP), and tris(pentafluorophenyl)borane (TPFPB) were added to a LiFSI-DME / DOL (2∶1) electrolyte, with each additive having a mass fraction of 2 wt% of the total electrolyte mass, to prepare an electrolyte of “2MLiFSI-DME / DOL (2∶1) + 2%LiNO3 + 2%LiDFOB + 2%TPFPP + 2%TPFPB”. Subsequently, lithium symmetric cells (Li||Li), lithium asymmetric cells (Li||Cu), and lithium full cells (Li||LFP) were assembled according to the same method as in Examples 1 and 2 to evaluate the effect of the multifunctional additives on the synergistic construction of fluorine-rich / inorganic-rich SEI on improving high current density cycling performance.
[0081] Assembling a button-type lithium symmetric battery: A battery casing of model 2025 and a polyethylene separator were selected. Both the negative and positive electrodes used lithium sheets with a thickness of 150-300μm. The polyethylene separator was placed between the positive and negative electrodes, and 50μL of the prepared electrolyte was dropped onto each side. Finally, the battery was encapsulated to obtain a button-type lithium battery. The assembled battery was subjected to Li||Li symmetric battery cycle performance tests on a Newway testing instrument under the test conditions of 1mA / 1mAh and 5mA / 5mAh. The results for 2M LiFSI-DME:DOL-2:1+2%LiNO3+2%LiDFOB+2%TPFPP+2%TPFPB are as follows... Figure 5 As shown, it can be stably cycled for 1300h and 500h at 1mA / 1mAh and 5mA / 5mAh, respectively.
[0082] Assembling a button-type lithium asymmetric battery: A battery casing of model 2025 and a polyethylene separator were selected. The negative electrode used a lithium sheet with a thickness of 150-300μm, and the positive electrode was copper foil. The polyethylene separator was placed between the positive and negative electrodes, and 50μL of the prepared electrolyte was dropped onto each side. Finally, the battery was encapsulated to obtain a button-type lithium battery. The assembled battery was subjected to Li||Cu asymmetric battery cycle performance tests on a Newway testing instrument. The test conditions were 1mA / 1mAh, 2mA / 2mAh, 5mA / 5mAh, and 10mA / 10mAh. The results for 2M LiFSI-DM E:DOL-2:1+2%LiNO3+2%LiDFOB+2%TPFPP+2%TPFPB are as follows... Figure 6 As shown, the electrolyte can be stably cycled for 1400 hours at 1 mA / 1 mAh and is still cycling, 1000 hours at 2 mA / 2 mAh, and 700 hours and 120 hours at 5 mA / 5 mAh and 10 mA / 10 mAh, respectively. It can be seen that the performance of the electrolyte is greatly improved after adding the additive, especially under high current conditions.
[0083] Assembling a button-type lithium-ion battery: A battery casing of model 2025 and a polyethylene separator were selected. A lithium sheet with a thickness of 150-300 μm was used as the negative electrode, and LFP was used as the positive electrode. The polyethylene separator was placed between the positive and negative electrodes, and 50 μL of the prepared electrolyte was dropped onto each side. Finally, the battery was encapsulated to obtain a button-type lithium-ion battery. The assembled battery was subjected to Li||LFP cycle performance testing on a Newway testing instrument under 0.1C and 1C conditions. Under 0.1C conditions, the coulombic efficiency remained above 99% after 180 cycles, but the capacity retention was also above 95%. Under 1C conditions, the coulombic efficiency remained above 99% after 380 cycles, but the capacity retention was only 75%.
[0084] Example 4:
[0085] Based on the multifunctional additive system (2wt% LiNO3 + 2wt% LiDFOB + 2wt% TPFPP + 2wt% TFPB) in Example 3, this example replaces 1,3-dioxolane (DOL) in the binary solvent with the perfluorinated diluent 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), maintains the volume ratio of dimethoxyethane (DME) to TTE at 2:1, and retains LiFSI as the lithium salt at a concentration of 2 mol / L. -1 The electrolyte “2MLiFSI-DME / TTE(2∶1)+2%LiNO3+2%LiDFOB+2%TPFPP+2%TPFP B” was prepared and assembled into lithium symmetric cells (Li||Li), lithium asymmetric cells (Li||Cu) and lithium full cells (Li||LFP) in the same manner as in the previous examples to investigate the synergistic enhancement effect of perfluorinated diluent on high current density cycle life and energy density in a high-salt, high-additive system.
[0086] Assembling a button-type lithium symmetric battery: A battery casing of model 2025 and a polyethylene separator were selected. Both the negative and positive electrodes used lithium sheets with a thickness of 150-300μm. The polyethylene separator was placed between the positive and negative electrodes, and 50μL of the prepared electrolyte was dropped onto each side. Finally, the battery was encapsulated to obtain a button-type lithium battery. The assembled battery was subjected to Li||Li symmetric battery cycle performance tests on a Newway testing instrument under the conditions of 1mA / 1mAh and 5mA / 5mAh. The results for 2MLiFSI-DME:DOL-2:1+2%LiNO3+2%LiDFOB+2%TPFPP+2%TPFPB are as follows... Figure 8 As shown, it can cycle stably for 1900h and 1350h at 1mA / 1mAh and 5mA / 5mAh, respectively, and the cycling is very stable under high current and high stripping capacity.
[0087] Assembling a button-type lithium asymmetric battery: A battery casing of model 2025 and a polyethylene separator were selected. The negative electrode used a lithium sheet with a thickness of 150-300μm, and the positive electrode was copper foil. The polyethylene separator was placed between the positive and negative electrodes, and 50μL of the prepared electrolyte was dropped onto each side. Finally, the battery was encapsulated to obtain a button-type lithium battery. The assembled battery was subjected to Li||Cu asymmetric battery cycle performance tests on a Newway testing instrument. The test conditions were 1mA / 1mAh, 2mA / 2mAh, 5mA / 5mAh, and 10mA / 10mAh. The results for 2MLiFSI-DM E:TTE-2:1+2%LiNO3+2%LiDFOB+2%TPFPP+2%TPFPB are as follows... Figure 9 As shown, it cycled for 1150 hours at 1 mA / 1 mAh and 2 mA / 2 mA while still cycling, and also achieved 700 hours and 120 hours at 5 mA / 5 mAh and 10 mA / 10 mAh respectively. Compared to Example 3, it exhibits a longer cycle life under asymmetric high current.
[0088] Assembling a button-type lithium-ion full battery: A battery case of model 2025 and a polyethylene separator were selected. A lithium sheet with a thickness of 150-300 μm was used as the negative electrode, and LFP was used as the positive electrode. The polyethylene separator was placed between the positive and negative electrodes, and 50 μL of the prepared electrolyte was dropped onto each side. Finally, the battery was encapsulated to obtain a button-type lithium-ion battery. The assembled battery was subjected to Li||LFP cycle performance testing on a Newway testing instrument under the test conditions of 0.1C and 1C. Under the 0.1C test condition, the coulombic efficiency remained above 99% and the capacity retention was 95% after 40 cycles; under the 1C test condition, the coulombic efficiency remained above 99% and the capacity retention was 95% after 380 cycles. This is better than the performance of the full battery in Example 3, and the performance of both symmetric and asymmetric batteries has been improved.
[0089] Example 5:
[0090] This embodiment optimizes the additive ratio based on the binary solvent system (DME:TTE = 2:1) of Example 4: maintaining LiNO3 and LiDFOB at 2wt% each, increasing pentafluorophenoxycyclotriphosphazene (PFPN) to 6wt%, tris(pentafluorophenyl)borane (TPFPB) at 2wt%, and using LiFSI as the lithium salt, maintaining a concentration of 2 mol / L. -1 An electrolyte of “2MLiFSI-DME / TTE(2∶1)+2%LiNO3+2%LiDFOB+6%PFPN+2%TPFPB” was prepared and assembled into lithium symmetric cells (Li||Li), lithium asymmetric cells (Li||Cu), and lithium full cells (Li||LFP) using the same method as in the previous examples to evaluate the changes in cycling performance under high stripping capacity and high current density conditions after increasing the PFPN content.
[0091] Assembling a button-type lithium symmetric battery: A battery casing of model 2025 and a polyethylene separator were selected. Both the negative and positive electrodes used lithium sheets with a thickness of 150-300μm. The polyethylene separator was placed between the positive and negative electrodes, and 50μL of the prepared electrolyte was dropped onto each side. Finally, the battery was encapsulated to obtain a button-type lithium battery. The assembled battery was subjected to Li||Li symmetric battery cycle performance tests on a Newway testing instrument under the test conditions of 1mA / 1mAh and 8mA / 8mAh. The results for 2MLiFSI-DME:DOL-2:1+2%LiNO3+2%LiDFOB+6%PFPN+2%TPFPB are as follows... Figure 11 As shown, it can be stably cycled for 700h and 650h at 1mA / 1mAh and 8mA / 8mAh, respectively.
[0092] Assembling a button-type lithium asymmetric battery: A battery casing of model 2025 and a polyethylene separator were selected. The negative electrode used a lithium sheet with a thickness of 150-300μm, and the positive electrode was copper foil. The polyethylene separator was placed between the positive and negative electrodes, and 50μL of the prepared electrolyte was dropped onto each side. Finally, the battery was encapsulated to obtain a button-type lithium battery. The assembled battery was subjected to Li||Cu asymmetric battery cycle performance tests on a Newway testing instrument. The test conditions were 1mA / 1mAh, 2mA / 2mAh, 5mA / 5mAh, and 10mA / 10mAh. The results for 2MLiFSI-DM E:TTE-2:1+2%LiNO3+2%LiDFOB+6%PFPN+2%TPFPB are as follows... Figure 12 As shown, it can cycle for 700 h at 1 mA / 1 mAh and is still cycling, and for 500 h at 2 mA / 2 mAh, and for 300 h and 50 h at 5 mA / 5 mAh and 10 mA / 10 mAh, respectively. Its electrochemical performance under asymmetric high current is not as good as in Example 4.
[0093] Assembling a button-type lithium-ion battery: A battery casing of model 2025 and a polyethylene separator were selected. A lithium sheet with a thickness of 150-300 μm was used as the negative electrode, and LFP was used as the positive electrode. The polyethylene separator was placed between the positive and negative electrodes, and 50 μL of the prepared electrolyte was dropped onto each side. Finally, the battery was encapsulated to obtain a button-type lithium-ion battery. The assembled battery was subjected to Li||LFP cycle performance testing on a Newway testing instrument under 0.1C and 1C conditions. Under 0.1C conditions, the coulombic efficiency remained above 99% and the capacity retention was 98% after 40 cycles; under 1C conditions, the coulombic efficiency remained above 99% and the capacity retention was 95% after 380 cycles.
[0094] To further elucidate the effects of different solvent systems and functional additives on the ion transport and solvation structure of the electrolyte, electrochemical impedance spectroscopy was performed on the five electrolytes used in Examples 1–5. Figure 14 ) and Raman spectroscopy ( Figure 15 )contrast.
[0095] like Figure 14 As shown, the impedance of 2M LiFSI-DME:DOL-2:1 is 22Ω; followed by 2M LiFSI-DME with an impedance of 30Ω; and 2M LiFSI-DME:TTE-2:1+2%LiNO3+2%LiDFOB+2%TPFPP+2%TPFPB with an impedance of 48Ω. Compared to the components without additives, the impedance increases after adding additives. The impedances of 2M LiFSI-DME:TTE-2:1+2%LiNO3+2%LiDFOB+2%TPFPP+2%TPFPB and 2M LiFSI-DME:DOL-2:1+2%LiNO3+2%LiDFOB+2%TPFPP+2%TPFPB are 55Ω and 75Ω, respectively. The impedance decreases when using the TTE solvent component compared to the DOL solvent component, indicating that TTE acts as a diluent, improving ionic conductivity.
[0096] Furthermore, through Figure 15 Raman spectroscopy can distinguish the differences between several electrolyte solvation structures. By comparing the addition of additives with solvent replacement, it can be seen that the addition of additives mainly increases the structure at 780 cm⁻¹. -1 FSI at the location - The characteristic peak of the anion can be used to determine the solvation structure of the electrolyte. This is the peak position where contact ion pairs (CIPs) and aggregates (ACGs) account for a larger proportion.
[0097] In summary, the ether-based electrolyte of the present invention is a high-voltage electrolyte. By dissolving a high concentration of lithium salt in a solvent, the side reactions of lithium metal are reduced, forming a strong and tough SEI film rich in fluorine. At the same time, the addition of TTE reduces the viscosity of the electrolyte. Therefore, even in a supersaturated lithium salt electrolyte, the reactivity between lithium metal and the electrolyte will not be hindered due to excessive viscosity of the electrolyte.
[0098] It has the following significant advancements: (1) The present invention can be stably cycled under high currents of 1mA-1mAh and 5mA-5mAh. (2) The electrolyte of the present invention can achieve ultra-high energy density in lithium metal batteries and form a stable SEI rich in fluorine.
[0099] The above examples illustrate the present invention only to aid in understanding it and are not intended to limit the scope of the invention. Those skilled in the art can make various simple deductions, modifications, or substitutions based on the principles of this invention.
Claims
1. A novel ether-based electrolyte for lithium metal batteries, characterized in that, The electrolyte comprises a non-aqueous organic solvent system, lithium salt, and additives; The non-aqueous organic solvent system includes at least one of the following: ethylene glycol dimethyl ether, 1,3-dioxolane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, diethyl ether, propyl ether, butyl ether, tetrahydrofuran, tetrahydropyran, ethylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, diethyl carbonate, methyl ethyl carbonate, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether. The lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethyl)sulfonyl)imide, lithium difluorooxalateborate, lithium hexafluorophosphate, and lithium tetrafluoroborate. The additives include at least one of vinylene carbonate, fluorovinyl carbonate, propane sulfonate lactone, lithium nitrate, lithium difluorooxalate borate, tris(pentafluorophenyl)borane, tris(pentafluorophenyl)phosphine, and pentafluorophenoxycyclotriphosphazene.
2. The novel lithium metal battery ether electrolyte according to claim 1, characterized in that, The non-aqueous organic solvent system includes ethylene glycol dimethyl ether and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, wherein the volume ratio of ethylene glycol dimethyl ether to 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is in the range of 1-3:
1.
3. The novel lithium metal battery ether electrolyte according to claim 1, characterized in that, The concentration range of the lithium salt in the electrolyte is 0.1-5 mol / L.
4. The novel lithium metal battery ether electrolyte according to claim 1, characterized in that, The additives include lithium nitrate, lithium difluorooxalate borate, tris(pentafluorophenyl)borane, and pentafluorophenoxycyclotriphosphazene; the contents of lithium nitrate, lithium difluorooxalate borate, and tris(pentafluorophenyl)borane are all 2 wt% of the total mass of the electrolyte, and the contents of pentafluorophenoxycyclotriphosphazene are 2-6 wt% of the total mass of the electrolyte.
5. The method for preparing the novel lithium metal battery ether electrolyte according to any one of claims 1-4, characterized in that, include: Under an inert atmosphere, the solvents in the non-aqueous organic solvent system are mixed at a predetermined volume ratio and magnetically stirred at 20-35°C for 10-30 minutes to obtain a uniform solvent matrix. Lithium salt is added in batches while the solvent matrix is continuously stirred, the solution temperature is controlled at ≤40℃ and stirred for 0.5-2h until the lithium salt is completely dissolved; Add the additives sequentially and stir continuously for 12-48 hours to ensure they are fully dissolved and dispersed, thus obtaining the ether electrolyte.
6. The method for preparing the novel lithium metal battery ether electrolyte according to claim 5, characterized in that, The inert atmosphere is argon, nitrogen, or helium.
7. The method for preparing the novel lithium metal battery ether electrolyte according to claim 5, characterized in that, The ether electrolyte was filtered through a 0.20-0.45 μm polytetrafluoroethylene microporous membrane under an inert atmosphere.
8. The application of novel lithium metal battery ether electrolytes in lithium symmetric batteries, characterized in that, The negative and positive electrodes of the battery are both lithium metal sheets or lithium alloy sheets. The battery separator of the battery is made of polyethylene or polypropylene; The electrolyte of the battery is the novel lithium metal battery ether electrolyte as described in any one of claims 1-4.
9. The application of novel lithium metal battery ether electrolytes in lithium asymmetric batteries, characterized in that, The negative electrode of the battery is a lithium metal sheet or a lithium alloy sheet. The positive electrode of the battery is copper foil; The battery separator of the battery is made of polyethylene or polypropylene; The electrolyte of the battery is the novel lithium metal battery ether electrolyte as described in any one of claims 1-4.
10. The application of novel lithium metal battery ether electrolytes in lithium full batteries, characterized in that, The negative electrode of the battery is a lithium metal sheet or a lithium alloy sheet. The positive electrode of the battery is lithium iron phosphate; The battery separator of the battery is made of polyethylene or polypropylene; The electrolyte of the battery is the novel lithium metal battery ether electrolyte as described in any one of claims 1-4.